Diagnostic performance of the Gynecology Imaging Reporting and Data System for malignant adnexal masses. Issue 3 (12th April 2017) - Zhang, Tan; Li, Fangxuan; Liu, Juntian; Zhang, Sheng
Abstract: Objective: To evaluate the Gynecology Imaging Reporting and Data System (GI‐RADS) for diagnosis of malignant adnexal masses in a Chinese population. Methods: A retrospective study was conducted of patients who underwent evaluation of suspected adnexal masses at a hospital in Tianjin, China, between January 1, 2015, and January 31, 2016. Ultrasonographic diagnosis was based on the GI‐RADS classification—a standardized summary of imaging data that estimates the risk of malignancy—and compared with the final pathological diagnosis. Results: Among 242 patients, thick wall, solid papillary projection, solid area, central blood flow, ascites, and GI‐RADS classification were associated with malignancy ( P< 0.05 for all variables). The 263 masses evaluated were classified as GI‐RADS 2 (functional cyst; n=65), GI‐RADS 3 (benign neoplasm; n=68), GI‐RADS 4 (one or two morphological findings suggestive of malignancy; n=101), and GI‐RADS 5 (≥3 morphological findings suggestive of malignancy; n=28). Four malignant cases with false‐negative findings were misclassified as GI‐RADS 3, whereas 24 benign cases with false‐positive findings were misclassified as GI‐RADS 4. The sensitivity, specificity, false‐positive rate, false‐negative rate, accuracy, and Youden index of the GI‐RADS classification were 96.4%, 84.3%, 18.5%, 3.0%, 89.3%, and 80.7%, respectively. Conclusion: The GI‐RADS classification performed well in the diagnosis of malignant adnexal masses. Abstract : Analysis of clinicopathologic and morphological features demonstrated that the Gynecology Imaging Reporting and Data System performed well in the diagnosis of malignant adnexal masses.